Line-defect mediated formation of hole and Mo clusters in monolayer molybdenum disulfide. (18th January 2016) - Ryu, Gyeong Hee; Lee, Jongyeong; Kim, Na Yeon; Lee, Yeongdong; Kim, Youngchan; Kim, Moon J; Lee, Changgu; Lee, Zonghoon
Abstract: The production of hole and Mo cluster by electron beam irradiation in molybdenum disulfide (MoS2 ), which consists of S-Mo-S layers, is monitored over time using atomic resolution transmission electron microscopy. S vacancies are firstly formed due to knocking off of S atoms and then line defects are induced due to accumulation of S vacancies in MoS2 sheet instead of forming a hole. The line defects tend to be merged at a point and a hole is formed subsequently at the point. Mo atoms tend to be clustered discretely as a nano sheet along the edge of the hole due to difference in displacement threshold energy between Mo and S atoms under electron irradiation. After Mo clusters are nearly separated from MoS2 sheet, the clusters are transformed into body-centered cubic nanocrystal of Mo during prolonged electron beam irradiation. The line defect mediated formation of hole and Mo cluster only occurs within a single grain of monolayer MoS2 sheet.